The emerging role of copper in depression - Chen, Jinhua; Song, Wenping; Zhang, Wenzhou (Frontiers in Neuroscience, 2023)
Copper (Cu) is an essential trace element in the brain, and serves as an important cofactor for numerous enzymes involved in a wide range of biochemical processes including neurobehavioral, mitochondrial respiration, and antioxidant effects. Recent studies have demonstrated that copper dyshomeostasis is tightly associated with the development of depression by inducing oxidative stress and inflammatory responses. However, these findings remained controversial so far. Cumulative studies tended to show a positive association, while some other studies showed no association and even negative association between serum/plasma copper level and depression. Based on these conflicted results, it was speculated to due to the clinical features of the population, stages of the disease, severity of copper excess and types of specimens detected in these studies. In addition, there was an inverse association between dietary copper intake and depression. Furthermore, increasing copper intake can influence dietary zinc and iron intake to prevent and treat depression. Thus, copper supplementation may be a good measure to manage depression. This review provided a deeper understanding of the potential applicability of copper in the prevention and treatment of depression.